Puppet 5 Essentials - Third Edition. - Alfke, Martin (Packt Publishing, 2017)
A Guide to managing servers and automation About This Book Breeze through Puppet's key features and performance improvements to bring real advantages to your IT infrastructure Discover Puppet best practices to help you avoid common mistakes and pitfalls Examples to help you get to grips with Puppet and succeed with everyday IT automation Who This Book Is For This book targets experienced IT professionals and new Puppet uses, who will learn all they need to know to go from installation to advanced automation. Get a rapid introduction to the essential topics and learn how to build best practices for advanced automation with Puppet. What You Will Learn Understand declarative configuration management Make use of GIT-based deployment workflows Extend Factor with secure elements Create modular and reusable Puppet code Extend your code base with publicly available Puppet modules Separate logic from data by using Hiera Understand and develop Puppet Roles and Profiles In Detail Puppet is a configuration management tool that allows you to automate all your IT configurations, giving you control over what you do to each Puppet Agent in a network, and when and how you do it. In this age of digital delivery and ubiquitous Internet presence, it's becoming increasingly important to implement scaleable and portable solutions, not only in terms of software, but also the system that runs it. This book gets you started quickly with Puppet and its tools in the right way. It highlights improvements in Puppet and provides solutions for upgrading. It starts with a quick introduction to Puppet in order to quickly get your IT automation platform in place. Then you learn about the Puppet Agent and its installation and configuration along with Puppet Server and its scaling options. The book adopts an innovative structure and approach, and Puppet is explained with flexible use cases that empower you to manage complex infrastructures easily. Finally, the book will take readers through Puppet and its companion tools such as Facter, Hiera, and R10k and how to make use of tool chains. Style and approach This book aims to impart all the knowledge required to tap into not only the basics of Puppet, but also its core. The basic ideas and principles of Puppet-based designs are explored and explained. Sophisticated tools are presented to enable you to use Puppet efficiently and productively. Downloading the example code for this book. You can download the example code files for al ...